2014
DOI: 10.1016/j.aju.2014.05.001
|View full text |Cite
|
Sign up to set email alerts
|

The accuracy of three-dimensional bladder ultrasonography in determining the residual urinary volume compared with conventional catheterisation

Abstract: ObjectiveTo determine the accuracy of three-dimensional bladder ultrasonography (US, using the BVI 3000, Verathon, WA, USA) for determining the residual urinary volume, compared with the conventional catheterisation method.Patients and methodsWe conducted a cross-sectional study at day-care unit of a University hospital after obtaining approval from the Ethics Review Committee of the hospital. Thirty-four patients with lower urinary tract symptoms requiring cystometrography were included. The postvoid volume w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 20 publications
2
27
1
Order By: Relevance
“…A study found 3D showed excellent correlation with catheterised volumes, especially for volumes <200 mL. There was more of a difference with higher volumes but these were not statistically significant …”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…A study found 3D showed excellent correlation with catheterised volumes, especially for volumes <200 mL. There was more of a difference with higher volumes but these were not statistically significant …”
Section: Introductionmentioning
confidence: 97%
“…They are more user‐friendly than conventional two‐dimensional (2D) ultrasound and only require basic training. They are usually small and portable allowing for use on the ward at the bedside . The disadvantage of these scanners is that they do not always enable direct bladder imaging and therefore may lead to diagnostic errors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jalbani and Ather [33] noted that the bladder scan estimate is as accurate as catheterization for determining the PVR urinary volume. Its accuracy was also comparable when the urinary volume is <100 mL, and there was no signiicant efect of age, gender and body mass index.…”
Section: Post-void Residualmentioning
confidence: 99%
“…However, it is not considered useful in the evaluation of UI [33]. Ultrasound imaging can reliably be used to measure bladder neck and urethral mobility in cases of SUI but it is not routinely performed in the initial assessment of UI.…”
Section: Mri Pelvic Loor Ultrasound and Emgmentioning
confidence: 99%